REPRESENTASI ETNIS TIONGHOA DI INDONESIA DALAM FILM NGENEST - Carina Widyasmara, Ratih Meila; Sugiarica Joni, I Dewa Ayu; Dewi Pascarani, Ni Nyoman (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Become one of the recognized ethnic, even its position is listed in Pasal 2 UU Nomor 12 Tahun 2012 on the citizenship of the Indonesian Republic, do not make Chinese etnic get an equal treatment in the community. At least that is what Ernest Prakasa is trying to tell in the Ngenest film. In this film, Ernest as the director who also as the main character tries to describe how Chinese ethnic as a minority in the Indonesian society with all kinds of problems and impact that must be accepted. The purpose of this research is to find out the representation of Chinese ethnic in Indonesia in the film. Using qualitative descriptive approach as well as Roland Barthes semiotics analysis method. The result of this study indicate, there are particular treatments that must be accepted by Ernest because of his different cultural backgrounds and the labeling of ethnic Chinese from the community. Keywords : Film, Ngenest, Representation Chinese Ethnic, Semiotics